PENGEMBANGAN PERANGKAT LUNAK DENGAN MENGGUNAKAN PHP - KM. Syarif Haryana (STMIK Mardira Indonesia, Bandung, 2015)
PHP is a web-based programming language in which the system is implemented on the server side. PHP can be inserted between the HTML language scripts and other server side language arena, with it then PHP will be executed directly on the server. While the browser will execute the web page through which the server will then receive the display “results so